2018
DOI: 10.1371/journal.pone.0201585
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines demonstrate the interacting influence of central obesity with other cardiometabolic risk factors of metabolic syndrome in Hong Kong Chinese adults

Abstract: ObjectiveMetabolic syndrome (MetS) or prediabetes is a complex disorder that is defined by a clustering of cardiometabolic risk factors, including obesity, hypertriglyceridemia, reduced high-density lipoprotein (HDL) cholesterol, hypertension, and insulin resistance. Among cardiometabolic risk factors, central obesity plays a key role in the development of MetS through alterations in the secretion of adipokines and interacts with other MetS risk factors to unfavorably influence overall cardiometabolic risk. Ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 85 publications
(96 reference statements)
4
22
0
3
Order By: Relevance
“…For instance, it has been reported previously that adiponectin regulates GH secretion through adiponectin receptor followed by Ca 2+ signalling 37 . Consistent findings from our laboratory have also revealed an association between CO and reduced circulating adiponectin 38 . Table 2.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, it has been reported previously that adiponectin regulates GH secretion through adiponectin receptor followed by Ca 2+ signalling 37 . Consistent findings from our laboratory have also revealed an association between CO and reduced circulating adiponectin 38 . Table 2.…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, incretins have showed an anti-in ammatory, antioxidant and anti-apoptotic effect and they are major players on appetite and satiety, being also widely related with obesity [46]. Interestingly, serum levels of PAI-1, an inhibitor of brinolysis usually up-regulated in obesity [47] were not much affected in our patients. This could be caused by the hypocaloric diet prior bariatric surgery received by the patients that could have affected their metabolic pro le.…”
Section: Discussionmentioning
confidence: 55%
“…It is well known that hypertension and dyslipidemia induce increases in oxidative stress and inflammation. [32][33][34] Oxidative stress and inflammation make a vicious circle and contribute to endothelial dysfunction. 35 In the present study, we found associations of FBS with obesity and with increases in blood pressure and low-density lipoprotein cholesterol level.…”
Section: Discussionmentioning
confidence: 99%